Development of Learning Media Autoplay Studio 8 Favorite Animal Material for Class III SD/MI - Fajarisman Fajarisman; Nostalgianti Citra Prystiananta; Fitria Nur Hamidah; Ana Ariama (Linguistic, English Education and Art (LEEA) Journal, 2024)
Media is a teaching aid to convey messages to students during the learning process. The aim of the research is to develop Autoplay Studio 8 Media to find out the validity, practicality and effectiveness of Autoplay Studio 8 based learning media to overcome boredom in learning. This research adopted the Borg and Gall model with 10 stages which were made into 7 stages to develop English language learning media for class III with a total of 20 students at SD Negeri 3 Kandang Kapongan Situbondo. The material content is 98% and the presentation is 85% so that a total of 91% is in the very decent category. For media experts, there are several aspects that are assessed, including appearance (83%), menu (80%), coloring (73%), font (83%), implementation (83%), and a total of 81%. which is included in the very feasible category. Validation by educators who assessed several aspects of the curriculum was 93%, content was 85%, and media was 88%. If added up, the overall result is 88% in the very suitable category, while the results tested on media students are 90%, the material aspect is 90%, and the benefits aspect is 86%, so it is collected. The total is 90% so that the learning media using Autoplay Studio 8 with animal love material is suitable for use in learning activities, especially in class III elementary school, which is very helpful for explaining more in depth and can be developed in the form of smartphone software to be more effective and efficient. Keywords: Autoplay Studio 8, Love Animal, SD/MI